Metagenomic Analysis of the Gut Microbiota of Wild Mice, a Newly Identified Reservoir of Campylobacter - Song, Hyokeun; Kim, Junhyung; Guk, Jae-Ho; Kim, Woo-Hyun; Nam, Hajin; Suh, Jun Gyo; Seong, Je Kyung; Cho, Seongbeom (Frontiers in Cellular and Infection Microbiology, 2021)
Campylobacter, the most common etiologic agent of zoonotic gastroenteritis in humans, is present in many reservoirs including livestock animals, wildlife, soil, and water. Previously, we reported a novel Campylobacter jejuni strain SCJK02 (MLST ST-8388) from the gut of wild mice (Micromys minutus) using culture-dependent methods. However, due to fastidious growth conditions and the presence of viable but non-culturable Campylobacter spp., it is unclear whether M. minutus is a Campylobacter reservoir. This study aimed to: 1) determine the distribution and proportion of Campylobacter spp. in the gut microbiota of wild mice using culture-independent methods and 2) investigate the gut microbiota of wild mice and the relationship of Campylobacter spp. with other gut microbes. The gut microbiota of 38 wild mice captured from perilla fields in Korea and without any clinical symptoms (18 M. minutus and 20 Mus musculus) were analyzed. Metagenomic analysis showed that 77.8% (14 of 18) of the captured M. minutus harbored Campylobacter spp. (0.24–32.92%) in the gut metagenome, whereas none of the captured M. musculus carried Campylobacter spp. in their guts. Notably, 75% (6 of 8) of M. minutus determined to be Campylobacter-negative using culture-dependent methods showed a high proportion of Campylobacter through metagenome analysis. The results of metagenome analysis and the absence of clinical symptoms suggest that Campylobacter may be a component of the normal gut flora of wild M. minutus. Furthermore, linear discriminant analysis (LDA) showed that Campylobacter was the most enriched genus in the gut microbiota of M. minutus (LDA score, 5.37), whereas Lactobacillus was the most enriched genus in M. musculus (LDA score, −5.96). The differences in the presence of Campylobacter between the two species of wild mice may be attributed to the differential abundance of Campylobacter and Lactobacillus in their respective gut microbiota. In conclusion, the results indicate that wild M. minutus may serve as a potential Campylobacter reservoir. This study presents the first metagenomics analysis of the M. minutus gut microbiota to explore its possible role as an environmental Campylobacter reservoir and provides a basis for future studies using culture-independent methods to determine the role of environmental reservoirs in Campylobacter transmission.